2020
DOI: 10.1080/02701367.2020.1788203
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Physical Demands Among Offensive and Defensive Players in Elite Men Bandy

Abstract: Purpose: This study examined the physiological sport-specific demands (total distance, mean velocity, effective game time, and time in five velocity zones) in elite bandy players of offensive and defensive playing positions. Method: Data were collected with 10 Hz GPS-units in the Swedish Elite League during the season 2015/16. Ten male elite bandy players were examined during 13 matches. Data were analyzed with Independent Samples Test and with descriptive statistics. Result: Analysis showed that defensive pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…Data collected during the extra time of the match were not included in the analyses. The speed zones of 25-29.99 km•h −1 and ≥ 30 km•h −1 were based on previously defined published data from bandy [2] and recommendations by Sweeting et al [20]. Acceleration and deceleration were defined as follows: (1) the acceleration/deceleration had to reach a minimum of 1 m•S −2 to mark the start of the acceleration/deceleration event;…”
Section: Global Positioning System Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Data collected during the extra time of the match were not included in the analyses. The speed zones of 25-29.99 km•h −1 and ≥ 30 km•h −1 were based on previously defined published data from bandy [2] and recommendations by Sweeting et al [20]. Acceleration and deceleration were defined as follows: (1) the acceleration/deceleration had to reach a minimum of 1 m•S −2 to mark the start of the acceleration/deceleration event;…”
Section: Global Positioning System Analysismentioning
confidence: 99%
“…Bandy is a winter team sport played on ice with similarities to soccer. Previous studies have investigated the physical workload during elite bandy by measuring heart rate and velocity patterns during match-play [1,2]. Blomqvist et al [1] observed that elite bandy players reach a heart rate between 70-90% of their maximum and spend up to 27% of the time above the lactate threshold during match-play depending on the player's position.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations